2022
DOI: 10.1108/ejim-06-2022-0313
|View full text |Cite
|
Sign up to set email alerts
|

How do firms use virtual brand communities to improve innovation performance? Based on consumer participation and organizational learning perspectives

Abstract: PurposeIn the context of virtual brand communities (VBCs), based on self-determination theory and organizational binary learning (OBL) theory, this study investigates the direct and indirect effects of various dimensions of consumer participation (CP) on firm innovation performance (FIP) and the mediating role of OBL. By introducing the perspective of knowledge absorptive capacity (KAC), this study examines the moderating effect of KAC on the relationship between OBL and TIP.Design/methodology/approachIn this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 125 publications
(167 reference statements)
0
2
0
Order By: Relevance
“…This growth is fueled by the increasing number of individuals engaging with video games as a primary form of entertainment, which forecasts suggest will continue to rise (Statista, 2023). Amidst this booming market, the role of consumer participation in new product development (NPD) has garnered significant attention for its potential to enhance product relevance and brand perception Zheng et al (2024). Engaging consumers directly in the creation process not only democratizes product development but also serves as a strategic tool to increase the brand's attractiveness and consumer loyalty (Gordon et al, 2021;Tanev et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This growth is fueled by the increasing number of individuals engaging with video games as a primary form of entertainment, which forecasts suggest will continue to rise (Statista, 2023). Amidst this booming market, the role of consumer participation in new product development (NPD) has garnered significant attention for its potential to enhance product relevance and brand perception Zheng et al (2024). Engaging consumers directly in the creation process not only democratizes product development but also serves as a strategic tool to increase the brand's attractiveness and consumer loyalty (Gordon et al, 2021;Tanev et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Enterprises should regularly organize staff training, experience exchange meetings and visits, and carry out learning activities for employees. Zheng et al, (2022) showed in his research that organizational learning can help enterprises dig deep into existing knowledge and use new knowledge to enter new knowledge categories. They will encourage employees to continue to learn and innovate, so that employees can maintain long-term motivation to learn, and are willing to share and exchange knowledge and information within the organization, and promote the continuous transfer of intellectual resources within the organization.…”
Section: Resultsmentioning
confidence: 99%